Produção e caracterização de membranas poliméricas de ECOVIO®/PVP para liberação tópica de valerato de betametasona - Schons, Edina Liara (2024)
Psoriasis is one of the most common skin diseases in the world. Its main clinical manifestation is the presence of erythematous and pruritic plaques that affect approximately 90% of cases. Treatment of lesions results in an improvement in the quality of life of patients and is carried out mainly with the use of topical corticosteroids. As an alternative to conventional treatment of psoriasis, this work presents a study on the production and characterization of polymeric membranes containing betamethasone valerate produced by biaxial electrospinning. The selected polymers were PVP and ECOVIO®. In addition to being biocompatible and stable at pH and temperature, PVP has high solubility in water, resulting in rapid release of the incorporated drug. ECOVIO®, composed of PLA and PBAT polymers, has good mechanical properties and forms membranes with controlled drug release, due to its hydrophobic characteristics. The produced membranes were characterized by SEM, FTIR, TGA, DSC and XRD techniques. Good compatibility between the membrane components was observed, as well as increased drug solubility, observed in the in vitro release study. Additionally, PVP showed a rapid release profile, releasing approximately 90% of the active ingredient in 5 minutes, while the release from the ECOVIO® membrane occurred in a controlled manner over 24 hours. For the biaxial membrane, a faster initial release was observed in relation to that obtained in the ECOVIO® membrane, referring to the PVP portion of the membrane, followed by a controlled release for 24 hours, characteristic of the ECOVIO® portion. Thus, according to the results obtained, it can be concluded that the membrane produced is promising for the controlled release of betamethasone valerate.